Assessing the perception of University Malaysia Kelantan on gamification in financial education - Nor Shahida Abd Wahab (2024)
This study investigated the perception of students at University Malaysia Kelantan (UMK) regarding the integration of gamification in financial education, using Unified Theory of Acceptance and Use of Technology (UTAUT) theory. Data were collected from 382 respondents using a quantitative approach through survey methods. Findings showed that performance expectancy factors (p-value: 0.874) strongly influence students' propensity to adopt gamification to enrich their financial knowledge. The limitation of this study was the existence of biased data due to unbalanced data collection. Besides, its exclusive focus on the East Coast region, making it less applicable to the West Coast region. Therefore, this study can focus on a single faculty but with varying academic levels and conduct research on the West Coast as well to obtain accurate research findings. The education industry should emphasize the importance of gamification in modern education to enhance student understanding and inform innovative strategies. The results of this study contribute to the originality of the field of financial literacy, offering valuable insights for educators, policy makers, and researchers who aimed to refine financial education strategies through gamification.